Recent trend of increasing myopia can be traced to infancy. (July 2019) - Matsuda, Koji; Park, Keunsik
Abstract: In recent years, a trend has been noted for increasing numbers of myopia cases found globally, which could potentially be indicative of a bigger problem. However, the cause of this trend remains unknown and in addition, we have yet to be able to establish a reliable method for preventing the onset of myopia. Furthermore, previous myopia studies have not paid adequate attention to hyperopia. That is to say, it has been suggested that the development of refraction in infancy and the onset of myopia are distinct from emmetropization. However, myopia studies also need to focus on the development of refraction in infancy, which involves hyperopia. Based on this viewpoint, our new hypothesis is that the trend towards myopia is associated with changes during the infancy period. The supporting evidence for these changes can be found in four areas, epidemiology of hyperopia, relationship with body height, incidence of esotropia, and birth month research. If this hypothesis is true, we need to investigate why there has been a decrease in hyperopia patients rather than why there has been an increase in myopia patients.